Absolute Quantification of Proteins in the Eye of Drosophila melanogaster. Issue 23 (3rd September 2020) - Raghuraman, Bharath Kumar; Hebbar, Sarita; Kumar, Mukesh; Moon, HongKee; Henry, Ian; Knust, Elisabeth; Shevchenko, Andrej
Abstract: Absolute (molar) quantification of proteins determines their molar ratios in complexes, networks, and metabolic pathways. MS Western workflow is employed to determine molar abundances of proteins potentially critical for morphogenesis and phototransduction (PT) in eyes of Drosophila melanogaster using a single chimeric 264 kDa protein standard that covers, in total, 197 peptides from 43 proteins. The majority of proteins are independently quantified with two to four proteotypic peptides with the coefficient of variation of less than 15%, better than 1000‐fold dynamic range and sub‐femtomole sensitivity. Here, the molar abundance of proteins of the PT machinery and of the rhabdomere, the photosensitive organelle, is determined in eyes of wild‐type flies as well as in crumbs ( crb ) mutant eyes, which exhibit perturbed rhabdomere morphogenesis.